Pentatonik och kompositionsmetod hos Miklós Maros med utgångspunkt från Cinguettio (1995) - Rudén, Jan Olof (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2004)
When Miklós Maros (b. 1943, Pécs, Hungary) arrived in Sweden 1968 to take up studies in composition with Ingvar Lidholm, he already had a thorough training from Hungary in composing according to historical styles, and he was well acquainted with pentatonics which was prevalent in the folk music of Hungary and the neighbouring countries. The flute duet Cinguettio from 1995 is especially rewarding in uncovering the use of pentatonics and melodic structure. The form is additive consisting of repeated motifs and contrasted by new material. The polytonal style of this rapid piece gives the impression of waves of chord changes at semitone distances. Miklós Maros has created the impression of birds chirping. The essay shows how it is possible to achieve real contrast with very limited material, by casting the pentatonic material differently: as superimposed pentachords one semitone apart or as exclusively triadic structures.